The issue of the importance of incorporating values in school textbooks in the era of globalization: A sociological approach - Manaa, Amel; Djemili, Zeyneb (The International tax journal, 2025)
The article seeks to examine the importance of values and their integration into educational materials in the context of globalization. Values are often referenced in discussions that go beyond national issues to include individual behavior, functioning as key indicators for distinguishing between the lifestyles of individuals and groups. They reflect a specific culture of any society, including its system of values, since what most characterizes it is the level of preservation of this deeply rooted system and the external risks and transformative pressures it faces. Based on this, we will attempt to discuss the issue of incorporating values into school textbooks through a sociological approach to their cultural and social significance within human societies.